STUDENTS’ AND LECTURERS’ PERCEPTION ON ACADEMIC WRITING INSTRUCTION - Santi Oktarina; Emzir Emzir; Zainal Rafli (University of Kuningan, 2018)
The aim of this research is to gain the perception of students and lecturers toward academic writing instruction Indonesian language classes in Universitas Sriwijaya. This current research was a part of research and development study on Moodle-based teaching model for academic writing instruction in Indonesian language classes. The steps of research and development model was carried out using survey and content analysis. The research was conducted in Universitas Sriwijaya. Questionnaire, interview and focus-group discussion (FGD) were instruments to collect data. Meanwhile, both quantitative and qualitative data analysis was used to analyze the collected data. After analyzing data from questionnaire, both students and lecturers perceived that academic writing instruction in Indonesian language classes are good and proper. However, the data from interview and FGD showed that there were different views between students and lecturers regarding to academic writing instruction in Indonesian language classes.Keywords: perception, instruction, academic writing